Bivalirudin or Heparin Treatment During Transcatheter Valve Interventions: Where are we Now? - Mastoris, Ioannis; D. Dangas, George (Current Pharmaceutical Design, 2016)
While the main gist of research pertaining to TAVR procedure involves improvement of existing valve technologies, lower size delivery systems and post-procedure antithrombotic therapy, the optimal intra-procedure anticoagulation has not been sufficiently defined. Peri-procedural complications such as cerebrovascular events and bleeding are largely associated with the safety and efficacy of anticoagulation regimen. Current guidelines advocate the use of heparin for anticoagulation with a target activated clotting time ≥300 seconds and careful protamine infusion in patients with high estimated bleeding risk. In this setting bivalirudin, devoid of all undesirable properties of unfractionated heparin such as highly variable elimination time and heparin-induced thrombocytopenia, may represent an alternative option in the interventionist’s armamentarium. Initial experience with bivalirudin has been encouraging as shown in two observational studies in the context of TAVR and balloon aortic valvuloplasty. The need for bleeding events reduction is particularly pronounced in this population that exhibits an inherent high bleeding risk due to platelet and von Willebrand factor dysfunction. Nevertheless, data from randomized studies are needed to establish bivalirudin role during TAVR procedure.
Keywords: Transcatheter aortic valve replacement